The Impact of Virtual Interviewing During the COVID-19 Pandemic on the Residency Application Process: One Institution's Experience. (23rd September 2022) - Nilsen, Kari; Walling, Anne; Johnson, Mariah; Curran, Maggie; Irwin, Gretchen; Meyer, Mark; Unruh, Greg
Abstract : Purpose: To assess the impact of virtual interviewing during the COVID-19 pandemic on the residency application process and to compare applicant costs and time spent interviewing during the 2020–2021 application cycle with prior years. Method: Fourth-year medical students at the University of Kansas School of Medicine applying for first-year residency positions via the National Resident Matching Program Match completed an electronic 46-item survey after submitting their rank lists during each application cycle from 2015–2016 to 2020–2021. The authors used descriptive statistics and t tests to analyze and compare responses to demographics questions and questions regarding number of submitted applications, offered and completed interviews, ranked programs, costs, and time spent interviewing. They used thematic analysis to code respondents' narrative comments about the virtual interviewing experience. Results: From 2015–2016 to 2020–2021, 994 (of 1, 190; 83.5%) respondents completed the survey. From 2019–2020 to 2020–2021, the average total cost of applying to residency per applicant dropped by 3, 566 ( P < .001) and the average time spent interviewing dropped by 13.3 days ( P < .001). At the same time, the average number of applications per applicant dropped by 3.4, and applicants completed the same number of interviews and ranked 2.3 fewer programs, none of which were statistically significant differences. Narrative comments from 113 (79%) respondents in 2020–2021 revealed 4 themes related to virtual interviewing: convenience of time and cost, positive aspects of the process, negative aspects of the process, and overall impressions of the program. Conclusions: Virtual interviewing during the 2020–2021 application cycle resulted in an approximately 80% reduction in cost for applicants and an approximately 50% decrease in time spent interviewing compared with previous years but was not associated with large increases in number of submitted applications, completed interviews, or ranked programs. Applicants generally perceived virtual interviewing as positive although they raised notable concerns.